2018
DOI: 10.1016/j.celrep.2018.03.095
|View full text |Cite
|
Sign up to set email alerts
|

A Cyfip2-Dependent Excitatory Interneuron Pathway Establishes the Innate Startle Threshold

Abstract: Sensory experiences dynamically modify whether animals respond to a given stimulus, but it is unclear how innate behavioral thresholds are established. Here, we identify molecular and circuit-level mechanisms underlying the innate threshold of the zebrafish startle response. From a forward genetic screen, we isolated five mutant lines with reduced innate startle thresholds. Using whole-genome sequencing, we identify the causative mutation for one line to be in the fragile X mental retardation protein (FMRP)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(99 citation statements)
references
References 61 publications
5
94
0
Order By: Relevance
“…Behavioral switching from SLC to LLC during conditioning or habituation is associated with reduced excitability of the M-cell [Takahashi et al, 2017, Marsden and Granato, 2015]. Furthermore, forward genetic screens have shown that mutants of altered SLC-LLC reaction balance are associated with altered M-cell excitability [Marsden et al, 2018, Jain et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral switching from SLC to LLC during conditioning or habituation is associated with reduced excitability of the M-cell [Takahashi et al, 2017, Marsden and Granato, 2015]. Furthermore, forward genetic screens have shown that mutants of altered SLC-LLC reaction balance are associated with altered M-cell excitability [Marsden et al, 2018, Jain et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…To identify the gene disrupted in slow learner p174 mutants, we took a previously described whole genome sequencing (WGS) approach followed by homozygosity mapping 29,32,33 . This uncovered a premature stop codon (Y211*) in the huntingtin interacting protein 14 (hip14) gene, encoding a palmitoyltransferase (PAT) which catalyzes the addition of palmitate moieties to cysteine residues of 5 substrate proteins 34 .…”
Section: The Palmitoyltransferase Hip14 Regulates Habituation Learninmentioning
confidence: 99%
“…I-sceI transgenesis was performed as previously described 78 in 1-cell stage embryos from hip14+/-incrosses. Transgenic lines were identified as previously described 33 . Briefly, 24 hpf F1 offspring of G0-injected fish were placed into Eppendorf tubes and incubated at 37°C for 30 min, recovered in petri dishes for 60 min, and screened for mKate with a fluorescent stereomicroscope (Olympus MVX10).…”
Section: Zebrafish Husbandry Mutagenesis Transgenesis and Genotypingmentioning
confidence: 99%
“…We previously performed a forward genetic screen for regulators of the acoustic startle response [23][24][25][26]. In brief, using a high-speed camera and automatic tracking, individual F3 larvae were exposed to a series of startling stimuli (for details on mutagenesis and the breeding scheme to obtain F3 larvae see [23]).…”
Section: A Forward Genetic Screen For Regulators Of the Larval Startlmentioning
confidence: 99%
“…We previously performed a forward genetic approach to identify functional regulators of the acoustic startle response. This approach identified a distinct sets of genes with previously unrecognized roles critical for startle habituation [23,24], startle sensitivity [25], and sensorimotor decision making [26]. Here, we describe kinematic mutants identified from this screen that display defects in executing swim movements of the startle response.…”
Section: Introductionmentioning
confidence: 99%